A rare anomaly of the foot presented as polydactyly - Dhingra, Vikram Jeet Singh (Medknow Publications & Media Pvt Ltd, 2013)
Presence of one or more digit is called as polydactyly and may manifest singly or with other genetic disorders. The frequency of polydactyly varies widely among populations. It can occur as an isolated condition or as a feature of a congenital condition. Polydactyly is a rare condition, but still rare is in form of triple great toes. We describe a case in a 4-year-old child diagnosed as triphalangism foot with no other obvious visible anomaly. Osteoplasty-combined surgery, which was ideal for anatomical reconstruction. In a 16-month follow-up period child recovered very well.